Ivermectin-facilitated immunity in onchocerciasis. Reversal of lymphocytopenia, cellular anergy and deficient cytokine production after single treatment. - Soboslay, P T (1992)
A longitudinal investigation has been conducted into the cell-mediated immune responses of onchocerciasis patients after a single-dose treatment with ivermectin. Untreated patients tested for delayed cutaneous hypersensitivity (DCH) to seven recall antigens showed lower responses than infection-free control individuals (P less than 0.01), but 6 and 14 months after treatment DCH reactions increased to similar levels to those seen in the controls. The in vitro cellular reactivity to Onchocerca volvulus-derived antigen (OvAg) was reduced in untreated patients as compared with controls, and the lymphocyte blastogenic responses to OvAg and streptolysin-O clearly improved up to 14 months after treatment. Peripheral blood mononuclear cells (PBMC) from untreated patients produced IL-1 beta, tumour necrosis factor-alpha (TNF-alpha) and IL-6 in response to mitogenic stimulation with phytohaemagglutinin (PHA), only low levels of IL-1 beta, IL-2 and TNF-alpha in response to OvAg, but higher amounts of IL-4 and interferon-gamma (IFN-gamma) in response to OvAg than control individuals. After ivermectin treatment, the OvAg-induced production of IL-1 beta and TNF-alpha increased significantly 1 and 14 months after treatment. The PHA-induced production of IL-2 and IL-4 increased 1 month after treatment and remained significantly elevated until 14 months after treatment, whereas the OvAg-specific secretion of IL-2, IL-4 and IFN-gamma did not change after ivermectin treatment. Flow cytometric analysis of lymphocyte-subsets in the peripheral blood of untreated patients revealed a relative and absolute (P less than 0.01) diminution of CD4+ cells and a significantly smaller CD4+/CD8+ cell ratio as compared with controls. By 4 weeks after treatment and thereafter, CD4+ T cells increased relatively and absolutely (P less than 0.01); likewise there was an absolute increase in T-helper-inducer cells (CD4+CD45RO+) and a temporarily improved CD4+/CD8+ cell ratio (P = 0.001). The expression of the low-affinity receptor for IgE (CD23) on total lymphocytes decreased from 14% to 7% by 14 months after treatment. The CD8+ cells and CD3+TCR gamma delta + cells were higher in patients than in controls and both remained elevated until 14 months after treatment. These results suggest a distinctly improved cellular immunity in human onchocerciasis that was facilitated by ivermectin therapy.